Invasive Pneumococcal Disease in Children in Tonga. Issue 2 (February 2017) - Lutui, Flora; Grant, Cameron C.; Best, Emma; Howie, Stephen; Aho, George
Abstract : In Tonga, pneumococcal conjugate vaccine is not a scheduled immunization. We identified all children in Tonga with invasive pneumococcal disease from 2010 to 2013. The average annual invasive pneumococcal disease incidence rate was 113/100, 000 (<2 years), 50/100, 000 (<5 years) and 25/100, 000 (<15 years). The case fatality rate (<5 years) was 25%. The incidence rate and high case fatality rate indicate the need for pneumococcal conjugate vaccine.